Problematizando a formação dos(as) estudantes da graduação em direito sobre a lei “Maria da Penha” e a violência contra as mulheres - ARAÚJO, Ricardo Gabriel de (2018)
This research, linked to the research line named Public Policies in Education, Educational Practices and Diversity, aimed to problematize the training process of Law students, from a private university, located in the countryside of the state of São Paulo, in reference to the discussion on gender violence and violence against women. The research methodology was centered on the qualitative approach of an explanatory nature. Took part on this research the students that were newcomers and the concluding, specifically those enrolled in the first and last term of the law degree course, both frequenting night classes. The choice of these classes aimed to encompass students who were starting their initial training X students who were finishing the course, having the possibility to understand to what extent the research subject was approached in this process. Data collection was based on the application of a questionnaire with open questions, in addition to a focus group discussion, organized from the exhibition of the Brazilian movie named "Vidas Partidas". The obtained data were analyzed through the establishment of analytical units. Regarding the types of violence witnessed by the students, through the questionnaire, it was possible to highlight physical violence, verbal violence and even psychological violence against women. Attention was drawn to the fact that a significant proportion of the graduating students (37.70%) and newcomers (24.00%) mentioned that the victims did not seek any kind of support in the face of the violence experienced, given the fear of suffering new aggression or due to other factors, like the concern of maintaining their livelihood, as well as that of their offspring, the victims are silent. When questioned in the focus group if at some point in the academic training they participated in discussions on the historical process of violence and inequality against women, in addition to gender difference, all the participants were categorical, when asserting that they had not participated in any discussion related to the subjects presented. These aspects reveal gaps in the initial training of the future Law operators, which prevents them from identifying, for example, the historical facts that constituted patriarchalism, machismo, as well as the denial of gender discussions in our society.